The SmartAG partner: CCAFS East Africa Quarterly Newsletter, January - March 2017 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
We are pleased to share with you our SmartAg Partner newsletter, highlighting policy engagement and ongoing research in the first quarter of 2017.